Utilization of Arable Land as a School Extracurricular Program to Achieve Sustainable Development Goals in Metro Lampung - Dewi, Pramita Sylvia; Muhisom, Muhisom; Azizah, Alif Luthvi (STKIP Singkawang, 2024)
Utilizing cultivated land as an extracurricular program in schools is an initiative that is relevant to sustainable development goals. This research aims to explore and evaluate the positive impact of implementing the program on aspects of sustainable development. The research method involves main activities and data analysis to understand the impact and obtain the perspectives of the participants and relevant stakeholders. The implementation of this extracurricular program also brings social benefits, such as increasing collaboration between students, forming a responsible attitude towards the environment, and increasing awareness of sustainable development. In addition, involving students in agricultural activities can be a means of developing character and leadership. This research also identified several challenges, such as a lack of resources and support, as well as the need for program integration with the formal curriculum to ensure sustainability and sustainability of learning. Thus, the use of cultivated land as an extracurricular program in schools can be an effective strategy for achieving sustainable development goals, especially in the aspects of environmental education, agricultural skills, and developing social attitudes. Joint efforts are needed from the school, government, and community to ensure the sustainability and success of this program in the long term.